PERANCANGAN CETAKAN INJECTION MOLDING HANDPRESS MATERIAL KOMPOSIT PPHI DAN SERAT ALAM - Nuha Desi Anggraeni; Alfan Ekajati Latief; Ichsan Putera (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
Injection molding is a method of forming a thermoplastic that is heated until it melts and then injected with high pressure into the mold so that the thermoplastic material will harden in the mold. The type of injection molding used is the hand press type with a pressure capacity of 34.83 MPa and a barrel capacity of 273 cm3. The mold that will be designed is to make a tensile test specimen ASTM 3039, an Impact test specimen ASTM D 6110-04, and a bending test specimen ASTM D 695. Determination of the specimen pointing to the type of material used is a composite with a high impact polypropylene matrix (PPHI) and natural fibers of Ramie and pineapple leaves. The mold design will initially make 2 mold designs based on the flow of material entering the mold, with the material being tested is 100% PPHI. After getting the optimal one, the composite will test the optimal mold with different types of PPHI composite material and 10% different volume fractions of natural fiber. Namely, pineapple and Ramie fibers with the parameters used as references are fill of time, Pressure at end fill, and Temperature at end fill. In this study, it can be concluded that of the three specimens above, the pineapple leaf fiber has high pressure and temperature at the end fill compared to Ramie fiber.Abstrak ditulis dalam Bahasa Inggris, satu paragraf, memuat tujuan, metode penelitian yang digunakan dan hasil.